Can interactive platform of university science parks enhance the quality of university research outcomes? evidence from a difference-in-differences model - Guo, Tianbao; He, Aowei; Zhai, Lei; Yan, Shuyi (Frontiers in Physics, 2025)
This study aims to examine the effect of national-level university science parks on university research productivity and quality in China. The actions and intentions of different individuals have driven each participating department to achieve varying degrees of development. Using the Triple Helix Theory to analyze university-industry government interactions, a Difference-in-Differences model was used to evaluate the causal relationship between science park participation and university research outcomes. The analysis provided new evidence on the impact of economic policies on the research capabilities of universities. Analysis indicated that: (a) National-level university science parks significantly promoted the growth of research projects and academic publications in universities. (b) Geographically, their influence in eastern China was more pronounced on research output and paper publications. (c) Disciplinary analysis indicated a stronger effect on increasing paper publications in science and engineering universities. (e) Personnels’ perceived behavioral control anticipated negative emotions, and sense of community all have direct positive effects on innovative intentions. Personnels' innovative intentions have a direct positive effect on their innovative behaviors. Personnels' age, education level, and monthly income have heterogeneous effects on innovative behaviors. By analyzing the conclusion, this study provides new empirical evidence for the practical applications of the Triple Helix Theory, highlighting the strategic role of science parks and individuals in fostering academic research. Policy recommendations are offered to optimize university-industry collaboration and enhance research performance.